PENGARUH TRANSAKSI PIHAK-PIHAK ISTIMEWA TERHADAP KINERJA KEUANGAN PERUSAHAAN - Fransisca _ (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2014)
This study aimed to analyze whether there are significant transaction privileged parties, as measured by sales to the parties the purchase of the special and privileged parties to financial performance as measured by Return on Assets (ROA). This research use related parties transaction which is measured by selling and buying activities with related parties. The focus of this research is company performance measurement because net income is used to performance measurement or investment benefit measurement (return on investment) or earning per share. The sample using in this study were 224 manufactured companies listed on the Stock Exchange, with the study period 2010-2012 with purposive sampling method, because this companies producing goods until processing the final goods to be sold. The data used is secondary data obtained from the web BEI is through idx.co.id. The results of research show that sales to related parties does not significantly influence the company's financial performance, and the purchase of related parties have a significant effect on the financial performance of the company.Keywords: financial performance, related parties, related parties transactions, return on assets